Update on the Management of Obesity - Barboza-Beraún, Aurelio (2025)
Obesity, recognized as a disease by the WHO in 1948, is chronic and multifactorial, affecting millions of people. It isprimarily diagnosed by a BMI over 30 kg/m², though this method has limitations. Its prevalence has tripled since 1975, withgenetic, socioeconomic, and environmental factors contributing to its development. Treatment includes lifestyle changes,medications, and bariatric surgery, with recent advancements in pharmacotherapy showing favorable outcomes in weight lossand cardiovascular risk reduction. Common procedures, such as Roux-en-Y gastric bypass and sleeve gastrectomy, have shownsustained weight loss results, achieving 50-75% excess weight loss at 10 years. The SADIS bypass offers a low complication rateand better outcomes, with more than 80% excess weight loss at 10 years. Each of these procedures has different remission rates for associated metabolic diseases. Selecting the appropriate procedure must balance effectiveness with patient safety. All of these operations allow discharge within the first 24-48 hours, with patients returning to work 5-7 days post-surgery.